Technology Support for the Inclusion of Deaf Students in Special School Sukabumi City - Nugraha, Deden Novan Setiawan; Hermina, Nurul (Journal of ICSAR, 2024)
The COVID-19 pandemic brought rapid changes in various areas of life, including education and technology. One of the learning media that the deaf can use to improve their ability to compose sentence structures is I-CHAT (I Can Hear and Talk). I-CHAT is a portal that contains applications that function as tools for the deaf in language acquisition. In communicating, mastery of sentence structure is crucial. It is because with the correct sentence structure, other people will better understand what we are talking about, and besides that, communication becomes more effective and efficient. Communication barriers that occur in deaf children are caused by hearing impairment, which ultimately requires deaf children only to use sight to acquire their receptive language. This has an impact on the acquisition of imperfect or partial deaf children's receptive language because not everything they see can be understood. Therefore, if a deaf child makes a sentence, the sentence structure is sometimes wrong. This research aims to determine the use of I-CHAT in the preparation of sentence structures for deaf students at Inclusive School Sukabumi City. This research is experimental with a quantitative approach. The results of the research show that the use of I-CHAT can improve the ability to compose sentence structures for deaf children in Special School Sukabumi City.